Drawing Pedagogies in Higher Education: the Learning Impact of a Collaborative Cross‐disciplinary Drawing Course. (16th October 2016) - Lyon, Philippa; Letschka, Patrick; Ainsworth, Tom; Haq, Inam
Abstract: Drawing is taught in higher education across art and design but also, increasingly, in medical education, with a variety of aims and approaches. It is argued that there is a need, in both these disciplinary domains, to make more explicit the underpinning pedagogical approach to drawing and the impact that different approaches have on learning. The research described in this article focuses on an optional drawing course for undergraduate craft students and medical students. The course is run by the College of Arts and Humanities at a UK university and has a thematic focus on the human body. This qualitative case study sets out, in the context of selected theory about the teaching and learning of drawing, to explore what the learning impact of a particular collaborative model of teaching drawing was on a cross‐disciplinary student group. Findings included, with reference to Riley's framework of drawing pedagogies, that a range of philosophical and pedagogical ideas about drawing were blended from the teaching perspective in a way that enabled students from distinct disciplinary backgrounds to engage and learn. A shift was observed in students' perceptions of drawing, with both sets of students questioning previously held assumptions about the use and value of drawing within their learning. Life drawing and anatomy laboratory drawing, in particular, provoked deep and challenging reflections about different cultural conceptions of the human body and the practice of collaborative drawing, with dialogic reflection, enabling insights to be developed into different disciplinary epistemologies.